The impact of self-determination theory on academic engagement among vocational college students: An empirical study in Guangdong, China - Zheng, Zixia; Rahimi, Nik Hanis Zuraihan; Mohamad, Norhisham Binti (Edelweiss Applied Science and Technology, 2025)
This study, based on Self-Determination Theory (SDT), employs a cross-sectional research design and uses a questionnaire survey to investigate 297 students in a vocational college in Guangdong Province, China. It aims to explore the impact of the three basic psychological needs—autonomy, competence, and relatedness—on academic engagement among vocational college students. The results show that these three dimensions are significantly and positively correlated with academic engagement (autonomy: r = 0.875, p < 0.001; competence: r = 0.810, p < 0.001; relatedness: r = 0.802, p < 0.001) and can significantly predict it (autonomy: β = 0.571, p < 0.001; competence: β = 0.194, p < 0.001; relatedness: β = 0.167, p = 0.001). The study validates the applicability of Self-Determination Theory in vocational education and provides evidence for educational practice. It is recommended that vocational colleges pay attention to students’ psychological needs to enhance academic engagement.